2019
DOI: 10.26438/ijsrbs/v6i5.3947
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Endophytes from Traditionally Used Medicinal Plants of Manipur for Their Antimicrobial Activity An Impact towards Future Drug Discovery

Abstract: Antimicrobial resistance has been developing fast and continuing to challenge the world medical sector. New strategies are needed to address this challenge that is incurring huge loss on human life. Medicinal plants from the untapped rainforest of the North-East India has a huge potential to find microbes that produce novel biomolecules. Bioactive endophytes were isolated from traditionally used medicinal plants. Paenibacillus spp. from Millettia spp. in a fermentation broth has shown strong and broad-spectrum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…A gram-positive bacterium, P. peoriae IBSD35, isolated from the stem of M. pachycarpa Benth. retained antimicrobial activity against S. aureus ATCC 25923 ( DeFilipps and Krupnick, 2018 ; Ngashangva et al, 2019 ). Its optimum growth condition was observed at pH∼6.8 at 38°C in LB and BHI media.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A gram-positive bacterium, P. peoriae IBSD35, isolated from the stem of M. pachycarpa Benth. retained antimicrobial activity against S. aureus ATCC 25923 ( DeFilipps and Krupnick, 2018 ; Ngashangva et al, 2019 ). Its optimum growth condition was observed at pH∼6.8 at 38°C in LB and BHI media.…”
Section: Discussionmentioning
confidence: 99%
“…It was observed that high salt concentration impeded the further purification process. The enriched protein complex is purified with positively charged resin DEAE-C based on the biomolecule physiochemical characteristics and RP-HPLC ( Conlon, 2006 ; Ngashangva et al, 2019 ). The PR-HPLC purified sample was analyzed with LC-MS/MS ( Eng et al, 1994 ; Dancík et al, 1999 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations